Effect of Quarry Activities on Some Morphological Parameters of Two Maize Varieties (SWAN 1 and SAMMAZ 52) - Odiyi, Bridget; Maku, Olubukola; Ologundudu, Foluso Akinbode; Abiya, Sylvanus Efetobor (Biology, Medicine, & Natural Product Chemistry, 2023)
The effect of quarry activities on some morphological parameters of two maize varieties (swan 1 and sammaz 52) was investigated with the aim of determining the impact of quarry activities on some growth parameters of the maize varieties under study. The seeds were collected from the Seed Bank Department of the Ondo State Ministry of Agriculture, Akure, Ondo State. They were authenticated at the Herbarium unit of the Federal University of Technology, Akure, and the voucher was deposited. Soil samples were collected at 50m, 100m, 150m, 200m, and 250m from the quarry site and transferred to the laboratory for analysis. A screen house experiment was set up to house the pots. Seeds of SWAN 1 and SAMMAZ 52 were sown into perforated plastic pots (30 cm diameter and 33 cm depth) filled with 10 kg of quarry soil. The following morphological parameters were determined; shoot height, leaf area, plant dry weight, shoot dry weight, root dry weight, root-shoot ratio, leaf area, and determination of photosynthetic parameters especially chlorophylls a and b. The result revealed that at 50 meters from the quarry site, SAMMAZ 52, one of the maize varieties grown in soil taken from the site, had the highest shoot height (94 cm). which showed that plants growing in higher concentrations of dust pollution respond to nutrient stress by devoting more of their available carbon to shoot growth, resulting in elongated stems, were consistent with the observed higher shoot height in SAMMAZ 52, daily variations in photosynthetic activity and the rate of nitrogen uptake are to blame for these alterations in plant behavior. The efficiency with which plants use the available nutrients determines whether they will survive in an area where there is quarry dust. The observed higher biomass (3.84g) under SAMMAZ 52's management regime can be attributed to the best possible rates of photosynthesis and nutrient assimilation, as well as to the presence of more chlorophyll and larger leaf surfaces.